WATER, ITS PRESENT, ITS FUTURE: A LOOK BACK AT ‘LIQUIDITY, INC.’. BY HITO STEYERL - Dewa Ayu Eka Savitri Sastrawan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
“Liquidity, Inc.” is an unpredictable video art that plays for 30 minutes. What’s being shown by the artwork might not be something that we can relate to straight away, moreover in the context of Bali. However, this paper aims to pour the artwork back to another clean container, to look back at one of Hito Steyerl’s bizarrely montaged fictional documentaries. As water becomes a more and more important matter to talk, think and encounter within our daily lives in the changing climate, along with possible connections on Bali’s tirta (water) belief, this writing aims to give a perspective on how we could view water in its present and future, in Bali and beyond, through an artwork such as “Liquidity, Inc.”